MINIMALIST HOUSING UNITS. ECO AND SMART TRENDS (Innovation in Woodworking Industry and Engineering design, 2026)
Minimalist housing units are a contemporary tendency that has developed widely in recent years, motivated by changing lifestyles and demographics, global social, economic and environmental problems. This requires reconsideration of needs and requirements of society in connection to the living environment and its sustainable development. The aim of the scientific research is to evaluate the contemporary architectural forms of the small urban dwelling and its interior environment peculiarities. This research presents an analysis of innovative examples in the context of the minimalist housing unit and its affordability. The focus is on the development of the small urban dwelling both for the benefit of the contemporary consumer and as a tool for dealing with many global problems and environmental changes.